A QUALITATIVE STUDY ON INTEGRATING THE STEAM APPROACH TO ENHANCE INDONESIAN LANGUAGE SKILLS IN MI MAARIF 02 BAJING KULON - Dian Aditya Suryani; Abdul Wachid Bambang Suharto (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study explores the integration of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach into Indonesian language learning at MI Maarif 02 Bajing Kulon. Using a qualitative descriptive method, the research examines how STEAM-based learning affects students' language skills, creativity, and 21st-century competencies. Data were collected through in-depth interviews with teachers, classroom observations, and document analysis. The study found that project-based and inquiry-based learning models, which combined various STEAM disciplines, effectively enhanced students’ Indonesian language proficiency. For example, students engaged in activities such as designing water filtration systems and creating persuasive posters, which required them to apply language skills in real-world contexts. This interdisciplinary approach not only improved vocabulary and sentence structure but also fostered critical thinking, problem-solving, and collaboration. However, the study also identified challenges, including resource limitations and the need for teacher training in STEAM pedagogy. Despite these obstacles, teachers demonstrated creativity and adaptability, using available resources and peer collaboration to implement STEAM effectively. The findings suggest that integrating STEAM into language education can transform learning by promoting active engagement, enhancing language development, and preparing students for future challenges. The study concludes that STEAM-based language education holds significant potential for reforming teaching practices in MI Maarif 02 Bajing Kulon, contributing to the holistic development of students by fostering linguistic, cognitive, and social skills essential for the modern world. Keywords: STEAM, Indonesian language learning, and MI Maarif 02 Bajing Kulon.